PELATIHAN PENGOLAHAN BUAH NAGA MENJADI PRODUK OLAHAN CEMILAN BAGI MASYARAKAT NAGARI SULIT AIR KABUPATEN SOLOK - Renny Eka Putri; Muahammad Zacky; Muhammad Iqbal; Nadian Nadian; Vasya Azzahra Siona; Yuharfiandri Yuharfiandri; Ali Anwar Delimunthe; Dellia Asdinisa A.S; Gizhella Mulyani Putri; Kemal Muhammad Hiero (Jurnal Hilirisasi IPTEKS, 2023)
Dragon fruit is one of the natural resources with significant economic potential when processed into various products. This activity aims to process and utilize dragon fruit as a primary ingredient in making snacks and pastries for the community, particularly for the PKK groups in Nagari Sulit Air. The event took place in Nagari Sulit Air, Solok Regency. The execution method of this activity consisted of two stages: lectures and discussions, followed by a demonstration phase. The results showed a high level of enthusiasm and interest among the community in understanding and participating in the process of making snacks from natural dragon fruit during this event. The community also successfully grasped the process of making processed products from dragon fruit, such as dragon fruit sticks and pastries made from dragon fruit peels. The conclusion drawn from this activity is that it has the potential to enhance community-based businesses focusing on dragon fruit. As a suggestion for future service, it's recommended to provide guidance and ongoing support to the community in developing their dragon fruit processed product businesses. Through this activity, the goal is to empower the local economy by increasing the production and utilization of dragon fruit, thereby boosting the local economy. New business opportunities might emerge, such as establishing micro or small enterprises centered on dragon fruit processed products. The expectation is to achieve greater economic benefits due to increased demand for dragon fruit. A stable market and rising demand can elevate farmers' income levels.